2009
DOI: 10.1055/s-0028-1119414
|View full text |Cite
|
Sign up to set email alerts
|

Extended Endoscopic Endonasal Approach to the Skull Base

Abstract: The extended endoscopic endonasal approach is a promising minimally invasive alternative for selected cases with sellar, parasellar or clivus lesions. As techniques and technology advance, this approach may become the procedure of choice for most lesions and should be considered an option in the management of the patients with these complex pathologies by skull base surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 23 publications
1
31
0
1
Order By: Relevance
“…23 Numerous other groups have since illustrated the surgical anatomy and techniques important for successful endoscope-assisted access to the CS. 3,4,8,17,18,24,25 …”
Section: Discussionmentioning
confidence: 99%
“…23 Numerous other groups have since illustrated the surgical anatomy and techniques important for successful endoscope-assisted access to the CS. 3,4,8,17,18,24,25 …”
Section: Discussionmentioning
confidence: 99%
“…Until now, no new post‐operative cranial nerve or neurological deficits and no surgical mortality are reported following resection. Although reported results are scarce and regardless of which surgical approach is used, total removal is achieved in only 49.2–79% of reported cases 42 ; often, a second operation was needed to remove residual tumour 43–46 …”
Section: Indications For Eeamentioning
confidence: 99%
“…The advent of the endoscope promoted recent advancement of endonasal surgery, 6,23 and endoscopic endonasal surgery is gaining acceptance as a routine technique for skull base surgery. 5,6,9 The endoscope provides superb illumination, high magnification, a panoramic view, and the ability to "look around corners." During the past decade, anatomical studies of the medial cavernous sinus via endoscopy precipitated evolution of the endoscopic endonasal approach, 3,4,7,10,18,24 and several clinical studies have reported excellent surgical results for cavernous sinus tumors by this approach.…”
mentioning
confidence: 99%